1963
DOI: 10.1021/bi00904a030
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrogen Exchange Method Using Tritium and Sephadex: Its Application to Ribonuclease*

Abstract: A new method for measuring the hydrogen exchange of macromolecules in solution is described. The method uses tritium to trace the movement of hydrogen, and utilizes Sephadex columns to effect, in about 2 minutes, a separation between tritiated macromolecule and tritiated solvent great enough to allow the measurement of bound tritium. High sensitivity and freedom from artifact is demonstrated and the possible value of the technique for investigation of other kinds of colloidsmall molecule interaction is indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
2

Year Published

1971
1971
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(77 citation statements)
references
References 24 publications
1
74
0
2
Order By: Relevance
“…These advances, together with the development and commercialization of gel-filtration media, led to the accurate artifact-free tritium-gel-filtration HX technique [19], which dominated HX work for the next 20 years. A range of HX studies on proteins, nucleic acids, oligosaccharides, their synthetic analogs, and their multimolecular complexes followed.…”
Section: Hx Measurement: Functional Labeling Proteolytic Fragmentatimentioning
confidence: 99%
“…These advances, together with the development and commercialization of gel-filtration media, led to the accurate artifact-free tritium-gel-filtration HX technique [19], which dominated HX work for the next 20 years. A range of HX studies on proteins, nucleic acids, oligosaccharides, their synthetic analogs, and their multimolecular complexes followed.…”
Section: Hx Measurement: Functional Labeling Proteolytic Fragmentatimentioning
confidence: 99%
“…These thermodynamic results led to kinetic questions and efforts to establish the rates at which dsDNA molecules breathe (open and close) locally. The hydrogen-tritium exchange method, initially developed by Englander (15) to study the opening and closing of protein domains, was used to examine the rates of dsDNA breathing of sequences of varying composition at temperatures below T m (45,58). These experiments showed that base pairs do open and close spontaneously within dsDNA, presumably also transiently exposing potential ssDNA templating sequences to be trapped by polymerases or related helper proteins in the initiation of DNA replication and transcription.…”
Section: Where Is the Coding Information Located In The Dna And How Cmentioning
confidence: 99%
“…Nevertheless, the conformational analysis involves several approximations: (1) the relationship between the dihedral angle 0 (NH-CaH) and the measured three-bond coupling constant 3JHNCH (8,9)-a spectral parameter most useful when considered in combination with potential energy maps (10,11); (2) temperature (12) and solvent (13,14) dependences of chemical shifts and proton exchange rates (15)(16)(17) of peptide hydrogens as related to their solvent-exposed or solvent-shielded state.…”
mentioning
confidence: 99%